"Escape the Room" – a strategy for problem-based learning and student inquiry. Issue 3 (31st July 2019) - Pearcy, Mark; Guise, Eric; Heller, Dana
Abstract : Purpose: Problem-based learning (PBL) has long been a regular feature in professions outside K-12 education and is growing in social studies education in recent years. PBL is built around student inquiry into an "ill-structured" or "messy" problem (Wieseman and Cadwell, 2005, p. 11). These inquiries are open ended, largely autonomous and student driven (Savin-Baden, 2014). The collaborative nature of PBL scenarios allows students to work with real-world concepts and skills to solve problems (Ferreira and Trudel, 2012). This paper aims to discuss these issues. Design/methodology/approach: This paper describes an innovative strategy for PBL learning, an Escape the Room (ETR) activity centered on historical content knowledge – in this case, the First World War. The activity incorporates a series of ill-structured problems with the First World War as its historical context. Findings: The paper concludes with a discussion of the utility of PBL activities like "ETR" and possible applications in the classroom for teachers. Originality/value: There has been significant research in PBL activities but little in the specific application of "ETR" scenarios, a rising trend in commercially available activities. The potential for student inquiry and engagement is a rich field for social studies educators.